19. Allele and haplotype frequencies in patients with Hematopoietic stemcell transplantation in National Children’s Hospital - Binh, Nguyen Thanh; Anh, Pham Minh (Tạp chí Nghiên cứu Y học, 2023)
HLA (Human Leukocyte Antigen) gene is located on chromosome 6’s short arm, including several loci. HLA genotyping is necessary for transplantation, especially in hematopoietic stem cell transplantation. A cross-sectional study to determine the frequency of HLA-A, HLA-B, and HLA-DRB1 alleles of 122 patients admitted to the National Children’s Hospital for Hematopoietic stem cell transplantation from the year between 2010 and 2020. The patients’ HLA genotyping was performed by PCR-SSP method using Micro SSPTM Generic HLA Class I and II DNA Typing Tray (One Lambda). The results showed that the HLA-A locus has 12 alleles of which the highest frequency alleles are A*11 (24.18%), A*02 (23.36%), A*33 (20.90%), and A*24 (14.34%). HLA-B locus has 24 alleles in which the highest frequency alleles are B*15 (24.59%), B*58 (12.30%), B*07 (9.02%), and B*46 (8.20%). HLA-C locus has ten alleles of which the highest frequency alleles are C*03 (24.59%), C*07 (22.12%), and C*04 (13.52%). HLA-DRB1 locus has 13 alleles of which the highest frequency alleles are DRB1*12 (23.77%), DRB1*03 (11.07%), DRB1*15 (10.25%), and DRB1*09 & DRB1*07 (8.20%). There are 1984 haplotypes combined from 4 loci HLA-A, HLA-B, HLA-C, and HLA-DRB1, of which the highest frequency haplotypes are A*11/B*15/C*08/DRB1*12 (1.21%); A*33/B*58/C*03/DRB1*03 (1.06%); A*11/B*15/C*04/DRB1*12 (0.76%); A*11/B*15/C*04/DRB1*12 (0.71%), and A*11/B*15/C*03/DRB1*12 (0.71%). The study provides the frequencies of alleles and haplotypes of HLA genotypes in Hematopoietic Stem Cell Transplantation. This is very important information for choosing stem cell donors and establishing the stem cell bank.